Optimal price and pro rata decisions for combined warranty policies with different repair options - Matis, Timothy I.; Jayaraman, Raja; Rangan, Alagar (Taylor & Francis Inc, 2008)
A repairable product under a non-renewing combined warranty policy that is subject to a displaced log-linear demand function of the product's price and pro rata period length is considered. Expressions for the manufacturer's long-run average profit per unit time under replacement, minimal and general repair options are obtained. In addition, expressions for the stationary points and second-order conditions of the profit function are presented. Numerical illustrations that demonstrate optimal product pricing, pro rata length determination, and repair option selection to maximize the manufacturers, profit are given.
Keywords: minimal repair; general repair; pro rata warranty; combined warranty